Effects of Qigong combined with Wai Khru Muay Thai on cardiopulmonary responses in sedentary older adults: A randomized control trial - Yang, Guang; Premsri, Narisara; Tong-un, Terdthai; Nonsa-ard, Rujira; Aneknan, Ploypailin; Tunkamnerdthai, Orathai; Manimanakorn, Apiwan; Leelayuwat, Naruemon (Asia-Pacific Journal of Science and Technology, 2025)
This study investigated the acute and training effects of Khon Kaen Qigong (KKQ), which combines Qigong and Muay Thai, on the cardiopulmonary responses in older adults. There were two experiments: 1) acute effect: a 30-minute KKQ session (control group performed reading) at pre-intervention and, 2) training effect (post-intervention compared with pre-intervention): composed of two conditions: the single session of KKQ/reading and two tests of cardiorespiratory fitness and respiratory muscle strength. Training intervention consisted of a 60-minute KKQ/day, three days a week (the control group had a sedentary life) for 12 weeks. At pre-intervention, there were three days of the experiment: 1) familiarization with the KKQ session, 2) heart rate, blood pressure, pulmonary function, and expired gas collection in response to KKQ/reading, and, 3) the six-minute walk distance and respiratory muscle strength. Post-intervention, participants repeated the pre-intervention except familiarization day. We found that the training contributed to a greater six-minute walk distance compared to the control group (mean difference [95%CI]; 7.04 [-14.94, 29.02], p < 0.05). Compared to the reading, it increased oxygen consumption (p < 0.05) and decreased ventilatory efficiency (p < 0.05) during and after the 30-minute KKQ session. The acute KKQ session produced cardiopulmonary responses to a very low level. An improvement of walking distance and ventilatory efficiency were previously shown to be negatively associated with cardiovascular risk and mortality. Thus, KKQ could be an alternative exercise that should be promoted to enhance a healthy long life for the older participants.